Dynamics of currents in the Qiongzhou strait during spring and summer based on a numerical simulation - Zheng, Quanxin; Wang, Huiqun; Li, Song; Cao, Zhenyi; Bao, Min (Frontiers in Marine Science, 2024)
A high-precision three-dimensional hydrodynamic model based on the Semi-implicit Cross-scale Hydroscience Integrated System Model (SCHISM) was constructed to investigate the characteristics of residual currents in the Qiongzhou Strait during spring and summer. Results reveal an overall westward transport in the strait during spring and summer. However, the results also support the potential occurrence of transient eastward Eulerian residual currents, which should be evident predominantly at the surface in the central and eastern sections of the strait and mainly characterised by subtidal oscillations. The direction and intensity of these residual currents indicate a pronounced influence of pressure gradient forces on both sides of the strait. The eastward flow observed in spring may represent a compensatory mechanism resulting from the relaxation period of long-term easterly winds, whereas the generation of eastward residual currents in summer is influenced by wind stress curl differences in both the western and eastern areas of the strait. The direct impact of the summer monsoon on the flow field in the strait is relatively weak. Additionally, the direction and intensity of the residual currents in the strait exhibit potential interannual variations that are directly associated with interannual wind variations. This study provides valuable insights in relation to the ongoing discourse on the dynamics of residual currents in the Qiongzhou Strait.